FAMILIES WITH PURPOSE: AN EMERGING VISION OF SCHOOL SUPPORT - Wilson Pérez Mendoza; Eylen Sofia Moncada (LÍNEA IMAGINARIA, 2025)
"Families with Purpose: An Emerging Vision of School Support" represents an innovative approach that seeks to transform family participation in the educational process, recognizing families as active stakeholders who are aware of their role in their children's learning. This concept arises from the need to rethink traditional forms of involvement, which are often limited to passive attendance or compliance with formal requirements, in order to promote more meaningful participation oriented toward clear, shared objectives. In a broader sense, this article aims to analyze how families influence the development of academic performance through support processes. As an essay, it was determined that, from this emerging perspective, school support is conceived as an intentional process in which families articulate their values, expectations, and resources to actively contribute to their children's academic and personal development. This requires family leaders to reflect on what type of support they wish to provide, how they can do so effectively, and what specific goals they hope to achieve together with the school.